Repeated colonoscopic screening of patients with acromegaly: 15-year experience identifies those at risk of new colonic neoplasia and allows for effective screening guidelines. - Dworakowska, D; Gueorguiev, M; Kelly, P; Monson, J; Besser, G; Chew, S; Akker, SA; Drake, WM; Fairclough, P; Grossman, AB; Jenkins, P (2010)
OBJECTIVE: It is suggested that patients with acromegaly have an increased risk of colorectal cancer and pre-malignant adenomatous polyps. However, the optimum frequency with which colonoscopic screening should be offered remains unclear. DESIGN: To determine the optimum frequency for repeated colonoscopic surveillance of acromegalic patients. METHODS: We retrospectively reviewed the case records of all patients with acromegaly seen in our centre since 1992: 254 patients had at least one surveillance colonoscopy, 156 patients had a second surveillance colonoscopy, 60 patients had a third surveillance colonoscopy and 15 patients had a fourth surveillance colonoscopy. RESULTS: The presence of hyperplastic or adenomatous polyps was assessed in all patients, while one cancer was detected at the second surveillance. At the third surveillance, mean (+/-s.d.) serum IGF1 levels (ng/ml) in patients with hyperplastic polyps were significantly higher than those with normal colons (P<0.05). The presence of an adenoma rather than a normal colon at the first colonoscopy was associated with a significantly increased risk of adenoma at the second (odds ratio (OR) 4.4, 95% confidence interval (CI) 1.9-10.4) and at the third (OR 8.8, 95% CI 2.9-26.5) screens. Conversely, a normal colon at the first surveillance gave a high chance of normal findings at the second (78%) or third surveillance (78%), and a normal colon at the second colonoscopy was associated with normality at the third colonoscopy (81%). CONCLUSIONS: Repeated colonoscopic screening of patients with acromegaly demonstrated a high prevalence of new adenomatous and hyperplastic colonic polyps, dependent on both the occurrence of previous polyps and elevated IGF1 levels.